Occupational stress and well-being in military contexts - Harms, Peter D.; Perrewé, Pamela L. (Research in occupational stress and well being ;, 2018)
Volume 16 of Research in Occupational Stress and Well Being is focused on how stress and well-being shape the experiences of military personnel both in and out of the combat zone. The book examines the connections between life in or after the military and employee stress, health, and well being. Chapters in this volume include veterans' transitions into the workplace, work-family issues for military couples as well as children of parents in the military, post-traumatic stress disorder, psychopathy and emotion, the role of stress and well-being on performance in the military, resilience and stress interventions in military organizations and the use of drugs by soldiers and veterans as a coping mechanism for chronic pain. The book showcases the work of the best researchers and theorists contributing to this field to provide a multidisciplinary and international collection that gives a thorough and critical assessment of knowledge, and major gaps in knowledge, on occupational stress and well being with a view to shaping future research both in military and civilian research literatures.